Using 2D Resistivity Imaging Technique to Detect and Delineate Shallow Unknown Cavities In Al-Haqlaniyah Area, Western Iraq - Al-Jumaily, Osama H.; Abed, Ali M.; Ali, Kamal K. (Iraqi Journal of Science, 2022)
Basal breccia unconformity layer between Anah and Euphrates Formations in Al-Haqlaniyah area, Western desert, include enormous sinkholes and cavities usually cause severe damages to any kind of engineering facilities built over it. Two-dimensional resistivity imaging has been applied to detect the depth and extent of the subsurface caves at five stations. The dipole-dipole array is chosen with an electrode spacing of 2 meters. 2D Dipole-dipole imaging inverse models show the resistivity values have a big variation between the anomalous background resistivity of rocks and part of cavities. These models showed shallow cavities at 1 to 3 m depth and others at 5to 6 m depth and extending to a depth of 23 m. The unconformity layer is less cohesive than the rocks beneath and above it. So it was the best area for the caves to be formed as a result of dissolving its rocks by leaking rainwater and groundwater. Therefore, it must be a pre-engineering preparation before starting any urban construction of the population in the study area or adjacent areas to avoid risks.